Synthesis and Characterization of Some Transition Metal Complexes of Schiff Base Derived From 2, 4 – Dihydroxybenzaldehyde: Synthesis and characterization of some transition - Vijayalakshmi, Mariyappana (Iranian Journal of Pharmaceutical Sciences, 2019)
New N2O2 type Schiff base has been designed and synthesized by condensing 2, 4 dihydroxy benzaldehyde and α-naphthylamine in ethanol. Solid metal complexes of the schiff base with Cu(II), Ni(II) and Zn(II) metal ion were synthesized and characterized by elemental analysis, magnetic susceptibility, molar conductance, IR, UV-Vis and ‘H NMR spectral studies. The data shows that the complexes have the composition of ML type.The UV-Visible and magnetic susceptibility data of the complexes suggest a square-planar geometry around the central metal ion except Zn (II) complex which has tetrahedral geometry. The redox behaviour of the complexes was studied by Cyclic Voltammetry. The in vitro activities of the compounds were tested against Staphylococcus, Bacillus subtilis, Escherichia Coli and Pseudomonas by well-diffusion method and antifungal of the compound were tested against fungi such as Aspergillus niger, Aspergillus flavus and Rhizoctonia bataicola by minimum inhibitory concentration. All the metal complexes showed stronger antifungal and antimicrobial activities than the free ligand.